2012
DOI: 10.1371/journal.pone.0043199
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin B Receptors Contribute to Retinal Ganglion Cell Loss in a Rat Model of Glaucoma

Abstract: Glaucoma is an optic neuropathy, commonly associated with elevated intraocular pressure (IOP) characterized by optic nerve degeneration, cupping of the optic disc, and loss of retinal ganglion cells which could lead to loss of vision. Endothelin-1 (ET-1) is a 21-amino acid vasoactive peptide that plays a key role in the pathogenesis of glaucoma; however, the receptors mediating these effects have not been defined. In the current study, endothelin B (ETB) receptor expression was assessed in vivo, in the Morriso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 70 publications
2
69
2
Order By: Relevance
“…41,42 In addition, it is worth mentioning that through ETB-R, ET-1 contributes to retinal ganglion cell loss in rat models of glaucoma and optic nerve injury. 23,43 Moreover, progressive retinal neurodegeneration Figure 6. A) Retinal glutamate levels from db/db mice treated with vehicle (black bar; n = 6), db/db mice treated with CaD (grey bar; n = 6), and non-diabetic (db/+) mice (white bar; n = 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 In addition, it is worth mentioning that through ETB-R, ET-1 contributes to retinal ganglion cell loss in rat models of glaucoma and optic nerve injury. 23,43 Moreover, progressive retinal neurodegeneration Figure 6. A) Retinal glutamate levels from db/db mice treated with vehicle (black bar; n = 6), db/db mice treated with CaD (grey bar; n = 6), and non-diabetic (db/+) mice (white bar; n = 6).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important issue because ET-1 exerts its functions via binding to two classes of G-protein coupled receptors: endothelin A (ETA) and endothelin B (ETB) receptors, both expressed in the retina. 21,22 Notably, ETB receptor expression has been reported in retinal neurons 23 and could be a key mediator of the neurodegenerative effects of ET-1 in the diabetic retina. Therefore, the inhibition of ET-1 could lead not only to an improvement in microvascular hemodynamics in the retina, but also an amelioration of the retinal neurodegeneration associated with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic retinopathy, increased level of retinal ET-1 and activation of ET A receptors are associated with vascular pathology, decreased retinal blood flow, and neurodegeneration [7,24]. Activation of ET B receptors induces retinal ganglion cell death in experimental glaucoma and after optic nerve injury [26,39]. Overexpression of endothelial ET-1 in mice contributes to glutamate toxicity and water accumulation in the inner ischemic retina resulting in retinal edema [6].…”
Section: Animals and Experimental Diabetesmentioning
confidence: 99%
“…Because activation of ET B contributes to the retinal ganglion cell loss in glaucoma and after optic nerve injury [26,39], it has been suggested that ET receptor antagonists may be useful as neuroprotective agents for the treatment of glaucoma [36]. …”
Section: Cellular Localization Of Et Receptor Proteinsmentioning
confidence: 99%
“…This could be important for explaining not only the improvement in microvascular hemodynamic, but also the amelioration of retinal neurodegeneration associated with diabetes. In this regard, it should be noted that endothelin has recently been shown to be involved in diabetes-induced neuroretinal degeneration and, therefore, its inhibition seems a promising therapeutic target in DR [82][83][84].…”
Section: Calcium Dobesilatementioning
confidence: 99%